Gothic incest Gender, sexuality and transgression - DiPlacidi, Jenny (Manchester University Press, 2018)
The first full-length study of incest in the Gothic genre, this book argues that Gothic writers resisted the power structures of their society through incestuous desires. It provides interdisciplinary readings of incest within father-daughter, sibling, mother-son, cousin and uncle-niece relationships in texts by authors including Emily Brontë, Eliza Parsons, Ann Radcliffe and Eleanor Sleath. The analyses, underpinned by historical, literary and cultural contexts, reveal that the incest thematic allowed writers to explore a range of related sexual, social and legal concerns. Through representations of incest, Gothic writers modelled alternative agencies, sexualities and family structures that remain relevant today.